How reliable is your hospital? A qualitative framework for analysing reliability levels. Issue 9 (21st March 2011) - Ikkersheim, David E; Berg, Marc
Abstract : Objective: Many approaches and methods have been developed to reduce errors in the healthcare delivery process and to increase patient safety. One of the approaches suited to improve patient safety is reliability theory. This paper adds a qualitative dimension to the application of reliability theory in hospitals. Based on a review of the literature, the authors identified a framework of qualitative elements that can be used to diagnose, understand and thereby improve upon the level of reliability in (department of) a hospital. Results: Based on the literature search, the authors identified four interconnected elements that are crucial for hospital reliability. These four elements are: process optimisation and standardisation; outcome measurement and monitoring; responsibilities and accountability of medical professionals; and organisational culture. Discussion: Substantial effort has been made in the last decade to improve patient safety. The actual improvement in safety has been fairly modest, which is understandable because most hospitals currently have fairly unreliable processes in place. Using the framework presented here, hospitals can gauge the reliability of their processes and practices. Recognisable characteristics provide insights into where improvement is needed and possible. In addition, this framework provides a way to view the relationship between different patient safety building blocks and a means to link them conceptually. An integrated approach is needed for hospitals to achieve a higher reliability level with particular attention to the interconnected elements that affect patient safety.